092x+3=x-.2

Simple and best practice solution for 092x+3=x-.2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 092x+3=x-.2 equation:


Simplifying
92x + 3 = x + -0.2

Reorder the terms:
3 + 92x = x + -0.2

Reorder the terms:
3 + 92x = -0.2 + x

Solving
3 + 92x = -0.2 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
3 + 92x + -1x = -0.2 + x + -1x

Combine like terms: 92x + -1x = 91x
3 + 91x = -0.2 + x + -1x

Combine like terms: x + -1x = 0
3 + 91x = -0.2 + 0
3 + 91x = -0.2

Add '-3' to each side of the equation.
3 + -3 + 91x = -0.2 + -3

Combine like terms: 3 + -3 = 0
0 + 91x = -0.2 + -3
91x = -0.2 + -3

Combine like terms: -0.2 + -3 = -3.2
91x = -3.2

Divide each side by '91'.
x = -0.03516483516

Simplifying
x = -0.03516483516

See similar equations:

| 3(t-2)=4t-8 | | 14f+2=.5(28f+4) | | Y+10=17y | | 25+3x=100 | | -(1+3v)=2(-2-2v) | | 24s^2-38s-7=0 | | 8w+6-12w=-14+w | | 6X+13=X | | 3x-10=x-2 | | -2/3=6+v/3 | | 1.06y-3=.7 | | 6x+12-x=62 | | -2/3=6+b/3 | | -(1+4x)=-14-x | | 6x+5=3x+14 | | 8X+10=13X-15 | | 37*47+37*3= | | 2(x+1)-4x+2=-2x+4 | | 3(n+2)=2n | | -243=-9[10+x] | | 12(x+3)=4+12x+20 | | x(4x)=3*4*3 | | 4-(8-9x)-17x= | | 7+7=4x-2 | | 6x+7-2x-12=9x+15 | | 5(-6n-1)-8n=147 | | a^2-14a+72=0 | | .75(4x-16)=3x-12 | | a^2+14a+72=0 | | 5x+2(x+8)=93 | | q-(-6)=2 | | 2x-4+9x-4=4x+7x+8 |

Equations solver categories